Prognostic Significance of Active and Modified forms of Endothelin 1 in Patients with Heart Failure with Reduced Ejection Fraction - Gottlieb, Stephen S. (Clin Biochem, 2014)
OBJECTIVES: Concentrations of endothelin I (ET1) are elevated in CHF patients, and, like other biomarkers that reflect hemodynamic status and cardiac pathophysiology, are prognostic. The Singulex assay (Sgx-ET1) measures the active form of ET1, with a short in-vivo half-life and C-terminal endothelin-1 (CT-ET1) is measured by the Brahms assay and is a modified (degraded) product with longer half-life. We aimed to determine the prognostic importance of active and modified forms of endothelin 1 (Singulex and Brahms assays) in comparison with other commonly measured biomarkers of inflammation, hemodynamic status and cardiac physiology in CHF. DESIGN & METHODS: Plasma biomarkers (Sgx-ET1, CT-ET1, NTproBNP, IL-6, TNFα, cTnI, VEGF, hs-CRP, Galectin-3, ST2) were measured in 134 NYHA class II and III CHF patients with systolic dysfunction. Prognostic importance of biomarkers for hospitalization or death were calculated by both logistic regression and Kaplan-Meier survival analyses. RESULTS: CT-ET1 (OR 5.2, 95% CI 1.7–15.7) and Sgx-ET1 (OR 2.9, CI 1.1–7.7) were independent predictors of hospitalization and death and additively predicted events after adjusting for age, sex and other significant biomarkers. Other biomarkers did not improve the model. Similarly, in Cox regression analysis, only CT-ET1 (HR 3.4, 95% CI 1.4–8.4), VEGF (2.7, 95% CI 1.3–5.4) and Sgx-ET1 (HR 2.6, 95% CI 1.2–5.6) were independently prognostic. CONCLUSIONS: Elevated concentrations of endothelin 1 predict mortality and hospitalizations in HF patients. Endothelin 1 was more prognostic than commonly obtained hemodynamic, inflammatory and fibrotic biomarkers. Two different assays of endothelin 1 independently and synergistically were prognostic, suggesting either complementary information or extreme prognostic importance.